Traction Control of Four Wheel Drive Heavy Duty Construction Machinery based on Flexible Work Surface - Chen Feng (Jixie chuandong)
To further study the property of heavy-duty construction machinery operation,the flexible work surface and the front and rear axle torque distribution are introduced,the construction machinery mathematical model of four-wheel drive heavy duty is established,a heavy-duty construction machinery traction integrated control strategy based on flexible work surface and the front and rear axle torque distribution control is got.The results show that by reducing the accelerator position can significantly eliminate the driving wheel excessive slip phenomenon in the motion process of the heavy duty machinery on the flexible work surface,the wheel speed is maintained near the target speed.After the introduction of traction control system,the wheel speed variation can be well suppressed within the range of fluctuation in the target drive wheel speed and the excessive slip phenomenon within the speed control range.After the introduction of the traction control system to eliminate obvious differences between the front and rear axle drive wheel speed,the front and rear axle drive force distribution is more reasonable.